(untitled) (Phenomenology, Humanities and Sciences, 2024)
The primary intention of this present study is introducing the notion of serenity as conceived by Heidegger. Considering that this intricate notion, drawn from the medieval mystical tradition, presupposes a preceding path traversed by Heidegger, we aim to succinctly present, in the introduction, some of the footprints of this journey: thus, we synthesize the existential analysis elaborated by the Philosopher of the Black Forest in Being and Time (2014/1927). This endeavor involved conducting a theoretical study, drawing upon the work of the German philosopher as the principal foundation, supplemented by commentaries as additional materials. The discussion unfolds in three parts: 1. Critique of modern-scientific thought. 2. Technique, Metaphysics, and Existential Attitude. 3. Serenity: gestures toward Psychology. Within this division, we address the origins of Greek rationality in its process of establishing Western rationality, as well as its intensification in modernity and its transformation within the horizon of technoscience. Confronting this historical process, we present phenomenological thought as a bridge that transitions humanity towards a distinct horizon. The notion of serenity holds a profound potential: it is capable of simultaneously affirming and negating the world of technique - it says yes, as it does not reject the presence of technique; yet it also says no, as it questions and denaturalizes it.